Spectral upward radiance and retrieved cloud properties - Trismono Candra Krisna (PANGAEA, 2018)
The data contain spectral upward radiance at wavelengths = 645 nm, 1240 nm, and 1640 nm. For SMART, the measured radiances have been convoluted with the MODIS relative spectral response. Retrieval products, one cloud optical thickness (645 nm), and two particle effective radius (1240 nm and 1640 nm), are given. For more details, please contact the corresponding author.
Supplement to: Krisna, Trismono Candra; Wendisch, Manfred; Ehrlich, André; Jäkel, Evelyn; Werner, Frank; Weigel, Ralf; Borrmann, Stephan; Mahnke, Christoph; Pöschl, Ulrich; Andreae, Meinrat O; Voigt, Christiane; Machado, Luiz A T (2018): Comparing Airborne and Satellite Retrievals of Optical and Microphysical Properties of Cirrus and Deep Convective Clouds using a Radiance Ratio Technique. Atmospheric Chemistry and Physics, 18(7), 4439-4462, https://doi.org/10.5194/acp-18-4439-2018